ALD preparation of high-k HfO2 thin films with enhanced energy density and efficient electrostatic energy storage. Issue 14 (26th January 2017) - Zhang, Le; Liu, Ming; Ren, Wei; Zhou, Ziyao; Dong, Guohua; Zhang, Yijun; Peng, Bin; Hao, Xihong; Wang, Chenying; Jiang, Zhuang-De; Jing, Weixuan; Ye, Zuo-Guang
Abstract : The energy density and energy efficiency deteriorate slightly from room temperature to 150 °C. Abstract : High- k dielectric HfO2 thin films with a predominant monoclinic phase were prepared by atomic layer deposition (ALD). The annealed HfO2 films exhibited a large dielectric constant, of up to ε r = 26 with a high breakdown field of over 4000 kV cm −1 . The best performance with a maximum recoverable energy density of 21.3 J cm −3 and energy efficiency of 75% was obtained with the 63 nm HfO2 films. In addition, a well-defined temperature dependence of the energy storage properties from room temperature to 150 °C was demonstrated, indicating a stable energy density variation between 11.0 and 13.0 J cm −3 with a high energy efficiency of about 80%. These achievements provide a platform for synthesizing high- k dielectric thin films with enhanced energy densities and efficiencies.